Analisis Sikap Terhadap Penyelidikan IPA, Kesenangan Dalam IPA dan Ketertarikan Berkarir Bidang IPA di SMPN 3 Batanghari - Nirmala Sari; Utari Prisma Dewi (Universitas Muhammadiyah Ponorogo, 2020)
The research design used was quantitative with the type of survey research. This study aims to describe the attitudes of students towards natural science learning at Junior High School 3 Batanghari reviewed through 3 indicators, namely attitudes toward inquiry in science, pleasure in science subjects, and interest in a career in science. The data collection technique used is total sampling with a total sample of 152 students. The research instrument used was an attitude questionnaire which explained the attitudes towards science learning through the three indicators as many as 25 statements. The data analysis technique used is descriptive statistics. Based on the results of data analysis, it was found that students in Junior High School 3 Batanghari in first dominant indicator were in sufficient category, the second dominant indicator was in good category and the third dominant indicator was in the good category.